2022
DOI: 10.35848/1347-4065/ac6f35
|View full text |Cite
|
Sign up to set email alerts
|

Kyropoulos growth of a 300 g SrB4O7 single crystal using a twin-type stirring blade

Abstract: We report the successful Kyropoulos growth of a large strontium tetraborate (SrB4O7, SBO) single crystal that weighs more than 300 g. In order to grow the large and transparent crystal, a new twin-type stirring blade was used along with a 150-mm-diameter crucible. The use of the stirring blade results in the production of the world’s largest SBO crystal with dimensions of 100 mm (a) × 30 mm (b) × 32 mm (c), a weight of 328.2 g, and a wide transparency down to 130 nm. These results will then lead to the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It was demonstrated that the crystal also had the highest surface acoustic wave velocity among piezoelectric crystals [10]. From the point of view of practical applications, note that a large single crystal of SBO with a weight of more than 300 g and transparency down to 130 nm can be grown [11]. Besides, SBO is a promising material for optical pressure sensors.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the crystal also had the highest surface acoustic wave velocity among piezoelectric crystals [10]. From the point of view of practical applications, note that a large single crystal of SBO with a weight of more than 300 g and transparency down to 130 nm can be grown [11]. Besides, SBO is a promising material for optical pressure sensors.…”
Section: Introductionmentioning
confidence: 99%